Approximating offset Curves using Bezier curves with high accuracy - Abedallah Rababah; Moath Jaradat (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, a new method for the approximation of offset curves is presented using the idea of the parallel derivative curves. The best uniform approximation of degree 3 with order 6 is used to construct a method to find the approximation of the offset curves for Bezier curves. The proposed method is based on the best uniform approximation, and therefore; the proposed method for constructing the offset curves induces better outcomes than the existing methods.